2011
DOI: 10.1128/cvi.05197-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Immunological Characterization of Three Potential Vaccinogens against Cryptosporidium Species

Abstract: Cryptosporidiosis is a ubiquitous infectious disease, caused by the protozoan parasites Cryptosporidium hominis and Cryptosporidium parvum, leading to acute, persistent, and chronic diarrhea with life-threatening consequences in immunocompromised individuals. In developing countries, cryptosporidiosis in early childhood has been associated with subsequent significant impairment in growth, physical fitness, and intellectual abilities. Currently, vaccines are unavailable and chemotherapeutics are toxic and impra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 40 publications
0
38
1
2
Order By: Relevance
“…In another study, three antigens, Cp15, profilin, and a Cryptosporidium apyrase, were delivered in a heterologous primeboost regimen as fusions with cytolysin A (ClyA) in a Salmonella live vaccine vector and as purified recombinant antigens, and were found to induce specific and potent humoral and cellular immune responses (Manque et al 2011). Profilin is a potent inducer of immune responses in mice by both Eimeria and Toxoplasma and works through the toll receptor TRL11.…”
Section: Vaccinesmentioning
confidence: 98%
“…In another study, three antigens, Cp15, profilin, and a Cryptosporidium apyrase, were delivered in a heterologous primeboost regimen as fusions with cytolysin A (ClyA) in a Salmonella live vaccine vector and as purified recombinant antigens, and were found to induce specific and potent humoral and cellular immune responses (Manque et al 2011). Profilin is a potent inducer of immune responses in mice by both Eimeria and Toxoplasma and works through the toll receptor TRL11.…”
Section: Vaccinesmentioning
confidence: 98%
“…This parasite is a potential life-threatening factor in patients with suppressed immune system, and can cause diarrhea (22,23). Currently, no specific, full, and effective treatment for cryptosporidiosis has been discovered (24). Surface and apical region antigens of the parasite such as cp23, gp900, gp15, gp40/15, gp40, and CSL are involved in the process of adhesion and invasion of Cryptosporidium sporozoite to target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mead and colleagues showed that oral administration of a Salmonella serovar Typhi vector encoding Cp23 and Cp40 led to specific immune responses against these antigens (102). More recently, Galen, Buck, Guerrant and colleagues developed a Salmonella serovar Typhi vector containing Cp15 and evaluated its efficacy via intranasal administration in well-nourished and malnourished mice infected with Cryptosporidium (103105)*. Unfortunately, disease course was not affected by immunization.…”
Section: Vaccine Developmentmentioning
confidence: 99%
“…Another promising screening technique is the use of “reverse vaccinology”, in which the Cryptosporidium proteome is mined in silico in order to identify potential surface proteins exposed to the immune system during infection. Buck and colleagues recently utilized this technique to identify several well-known and novel Cryptosporidium vaccine candidates, including Cp15, profilin and calcium apyrase (105)**. Mice vaccinated with a live Salmonella vector expressing these proteins developed strong, specific cell-mediated and humoral responses, suggesting that these antigens may elicit a protective immune response against Cryptosporidium and thus serve as effective vaccine targets.…”
Section: Vaccine Developmentmentioning
confidence: 99%